The Contribution of Forensic Science Experts Policies to Criminal Case Resolution - Yunianto, Eko; Yulius Sigit Kristanto; Yanto Mulyanto P; Robinson Pardomuan; Joman Rabah Mahfouth Alkhatib (Lembaga Contrarius Indonesia, 2026)
Scientific Crime Investigation constitutes a science-based investigative approach that utilizes forensic technology and expert analysis to uncover criminal acts. Despite its increasing use in criminal investigations, the legal position and evidentiary validity of Scientific Crime Investigation remain insufficiently regulated, resulting in normative ambiguity and inconsistent judicial practice. This research aims to examine the regulation of the role of Scientific Crime Investigation experts in the disclosure of criminal acts from the perspective of Pancasila justice, to identify weaknesses in the existing legal framework, and to formulate a reconstruction of regulatory norms governing the use of Scientific Crime Investigation in criminal proceedings. The study applies Pancasila justice theory, legal system theory, and progressive legal theory within a constructivist paradigm, employing a socio-legal research approach. Primary data reflecting legal realities in investigative and judicial practices and secondary legal materials were collected and analyzed using qualitative descriptive methods. The findings of this research reveal that, first, the absence of explicit legal recognition of Scientific Crime Investigation as valid evidence has resulted in normative uncertainty and recurring disputes regarding the reliability, admissibility, and probative value of scientific findings in judicial proceedings. Second, structural and institutional weaknesses continue to hinder the effective use of Scientific Crime Investigation, including limited forensic infrastructure, shortages of qualified human resources, inadequate understanding of scientific investigative methods, weak coordination between investigators and forensic experts, and high operational costs. Third, substantive and cultural weaknesses remain evident due to the lack of standardized norms governing scientific investigative outputs and public noncompliance with investigative procedures, which collectively compromise crime scene integrity and the credibility of scientific analysis. These findings demonstrate the necessity of normative reconstruction to formally integrate Scientific Crime Investigation into the criminal justice system in accordance with the values of Pancasila justice.